2020
DOI: 10.3389/fphar.2020.00216
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Proteomic Changes and Sirt1/AMPK Signaling Activation by Oxymatrine Treatment in Rats With Non-alcoholic Steatosis

Abstract: Background: Currently, active ingredients of herbal extracts that can suppress lipid accumulation in the liver have been considered a potential treatment option for nonalcoholic fatty liver disease. Methods: Steatosis rat model was created by high fat and high sucrose diet feeding and treated with oxymatrine (OMT). Serum biochemical parameters, liver histology and lipid profiles were examined. Hepatic differentially expressed proteins (DEPs) which were significantly changed by OMT treatment were identified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…However, the exact effect of the SIRT1/Nrf2 signaling pathway on NLRP3 inflammasome activation-mediated pyroptosis in atherosclerosis has yet to be reported. Notably, it has been confirmed that oxymatrine can activate the SIRT1 signaling pathway (28,29). Hence, the present study further explored the role of the SIRT1/Nrf2 signaling pathway in the protective effect of oxymatrine against ox-LdL injury and the inhibitory effect of oxymatrine on NLRP3 inflammasome activation-mediated pyroptosis in HUVEcs.…”
Section: Introductionmentioning
confidence: 57%
“…However, the exact effect of the SIRT1/Nrf2 signaling pathway on NLRP3 inflammasome activation-mediated pyroptosis in atherosclerosis has yet to be reported. Notably, it has been confirmed that oxymatrine can activate the SIRT1 signaling pathway (28,29). Hence, the present study further explored the role of the SIRT1/Nrf2 signaling pathway in the protective effect of oxymatrine against ox-LdL injury and the inhibitory effect of oxymatrine on NLRP3 inflammasome activation-mediated pyroptosis in HUVEcs.…”
Section: Introductionmentioning
confidence: 57%
“…Traditional surgery is no longer the preferred treatment for HCC, so new therapeutic directions need to be explored. 17 , 53 , 54 , 55 Molecular targeted therapy is an important topic for the treatment of HCC; however, the precise molecular mechanisms remain unknown. The development of high-throughput transcriptome sequencing technologies and the ceRNA hypothesis have been proposed, in which lncRNAs and mRNAs interact with each other through shared miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of SIRT1/AMPK signaling may prevent oxidative stress and inflammation during lipotoxicity-related hepatocyte injury ( Xu et al, 2020 ). SAA alleviates insulin resistance and HFD-induced NAFLD through AMPK activation ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%